Penentuan Letak Liang Gua Batu Tunggal Menggunakan Metode Geolistrik Konfigurasi Wenner di Desa Tegalrejo Kotabaru - Dwi Asmaul Husna; Sri Cahyo Wahyono; Simon Sadok Siregar (Lambung Mangkurat University Press, 2019)
Kotabaru Regency has a cast area with an area of 1.777,6303 km2 with a process of dissolving rocks of carbonate that extends to the coast of the Southeast part of the island of Borneo. The study sites are located in the Batu Tunggal cave at coordinates 3o 11 '41.8